Effect of cyclosporin A on interleukin-6 and soluble interleukin-2 receptor in patients with rheumatoid arthritis. Issue 2 (February 1995) - Crilly, A; Kolta, S; Dougados, M; Sturrock, R D; Amor, B; Capell, H A; Madhok, R
Abstract : OBJECTIVE--To investigate the effect of cyclosporin A (CyA) therapy on circulating concentrations of interleukin-6 (IL-6) and soluble interleukin-2 receptor (sIL-2R) in patients with rheumatoid arthritis (RA). METHODS--Twenty four RA patients with active disease were studied. Plasma was collected before and after 16 weeks of CyA treatment. IL-6 was measured by B9 bioassay and sIL-2R by enzyme linked immunosorbent assay (ELISA). RESULTS--The initial median IL-6 concentration of 165 IU/ml decreased significantly to 71 IU/ml after 16 weeks (p < 0.05). Similarly, the initial median plasma sIL-2R value of 665 U/ml decreased significantly to 570 U/ml (p < 0.05). This decrease was accompanied by an improvement in clinical parameters of disease activity. Some association between sIL-2R, IL-6, haemoglobin, and platelets was also observed. CONCLUSIONS--This study has demonstrated that, in vivo, CyA therapy in RA can significantly reduce circulating concentrations of IL-6 and sIL-2R. Modulation of both T and non-T cell derived cytokines may be one mechanism by which CyA improves rheumatoid disease. Whether this is a direct effect of CyA on the cells within the rheumatoid joint producing these cytokines or an indirect effect mediated by other cytokines which can influence IL-6 and Il-2R values remains to be determined.